1986
DOI: 10.1159/000226379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholic Acid on Tumor in the Egyptian Toad

Abstract: Egyptian toads, Bufo regularis, were fed with cholic acid (sodium salt) 3 times/week for 12 weeks at different dose levels (2.5, 5, and 10 mg/toad). Results obtained showed only 1 case in both the 5 and 10 mg/toad doses that gave a tumor. Toads receiving N-methyl-N-nitrosourea (MNU) 1 mg/toad, 3 times/week for 12 weeks had 36% ileum tumors (18 toads out of 50, without mortality). On the other hand, a higher dose of MNU (5 mg/toad) caused 50% mortality in the experimental animals. Toads treated with MNU at a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The results of the present investigation confirm our pre vious studies [12,13] which showed that DMBA induces liver tumors by light microscopy. Results obtained in the present work revealed that hepatocellular carcinomas in duced by DMBA appeared as circumscribed masses of crowded cells with focal necrosis at the center.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present investigation confirm our pre vious studies [12,13] which showed that DMBA induces liver tumors by light microscopy. Results obtained in the present work revealed that hepatocellular carcinomas in duced by DMBA appeared as circumscribed masses of crowded cells with focal necrosis at the center.…”
Section: Discussionsupporting
confidence: 91%
“…The models have in cluded Xenopus laevis [4][5][6], Rana pipiens [7,8] and Bufo regularis [9,10], Some investigators have shown that toads can be used as a model to study the development of carcinogens [11], cocarcinogens [12] and vitamins [13], In the majority of these studies, the diagnosis of the induced tumors was based essentially on light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Amphibian tumors have been studied by several workers (Khudoley & Picard 1980, Sadek 1981, 1986a). More recently, it has been reported that chemical carcinogens induced tumors in the Egyptian toad (Sadek 1986b, Sadek & Abdelmeguid 1986.…”
Section: Introductionmentioning
confidence: 99%